Heterogeneous clinicopathological findings and patient-reported outcomes in adults with MN1-altered CNS tumors: A case report and systematic literature review - Frederico, Stephen C.; Vera, Elizabeth; Abdullaev, Zied; Acquaye, Alvina; Aldape, Kenneth; Boris, Lisa; Briceno, Nicole; Choi, Anna; Christ, Alexa; Cooper, Diane; Grajkowska, Ewa; Kunst, Tricia; et al. (Frontiers in Oncology, 2023)
The uncommon MN1-altered primary CNS (central nervous system) tumors were recently added to the new World Health Organization 2021 classification under the name Astroblastoma, MN1-altered. “High-grade neuroepithelial tumor with MN1 alteration” (HGNET-MN1) has been another term used to describe them (albeit currently not recommended) and emerged after DNA methylation analysis of tumors previously known as CNS primitive neuroectodermal tumors. Thought to occur most commonly in children and predominantly in females, MN1-altered CNS tumors are associated with typical but not pathognomonic histological patterns and are characterized by a distinct DNA methylation profile and recurrent fusions implicating the MN1 (meningioma 1) gene. There is only partial overlap between the methylation class HGNET-MN1 and the morphological diagnosis of astroblastoma; most cases with morphological features of astroblastoma (but not all) show these molecular features, whereas not all tumors with MN1 fusions show astroblastoma morphology. Currently, no standard treatment has been established for MN1-altered tumors. Some patients experience multiple recurrences despite undergoing surgical resection, radiation, and chemotherapy, whereas others experience no recurrence after surgical resection alone, suggesting large clinical and biological heterogeneity despite unifying epigenetic features and recurrent fusions. In this report, we present the demographics, tumor characteristics, treatment, and outcome (including patient-reported outcomes) of three adults with MN1-altered primary CNS tumors diagnosed via genome-wide DNA methylation and RNA sequencing. All three patients were females and two of them were diagnosed as young adults rather than in their childhood. By reporting our neuropathological and clinical findings and comparing them with previously published cases we provide insight into the clinical heterogeneity of this tumor. Our work portrays a model for prospective, comprehensive, and systematic collection of neuropathological and clinical data that is aimed at improving the understanding of these and other newly described rare CNS tumors, incorporating histology, molecular and clinical features, treatment, survival, and patient experience.